Microelimination or Not? The Changing Epidemiology of Human Immunodeficiency Virus-Hepatitis C Virus Coinfection in France 2012–2018. (5th January 2021) - Cotte, Laurent; Hocqueloux, Laurent; Lefebvre, Maeva; Pradat, Pierre; Bani-Sadr, Firouze; Huleux, Thomas; Poizot-Martin, Isabelle; Pugliese, Pascal; Rey, David; Cabié, André; ,
Abstract: Background: The arrival of highly effective, well-tolerated, direct-acting antiviral agents (DAA) led to a dramatic decrease in hepatitis C virus (HCV) prevalence. Human immunodeficiency virus (HIV)-HCV–coinfected patients are deemed a priority population for HCV elimination, while a rise in recently acquired HCV infections in men who have sex with men (MSM) has been described. We describe the variations in HIV-HCV epidemiology in the French Dat'AIDS cohort. Methods: This was a retrospective analysis of a prospective cohort of persons living with HIV (PLWH) from 2012 to 2018. We determined HCV prevalence, HCV incidence, proportion of viremic patients, treatment uptake, and mortality rate in the full cohort and by HIV risk factors. Results: From 2012 to 2018, 50 861 PLWH with a known HCV status were followed up. During the period, HCV prevalence decreased from 15.4% to 13.5%. HCV prevalence among new HIV cases increased from 1.9% to 3.5% in MSM but remained stable in other groups. Recently acquired HCV incidence increased from 0.36/100 person-years to 1.25/100 person-years in MSM. The proportion of viremic patients decreased from 67.0% to 8.9%. MSM became the first group of viremic patients in 2018 (37.9%). Recently acquired hepatitis represented 59.2% of viremic MSM in 2018. DAA treatment uptake increased from 11.4% to 61.5%. More treatments were initiated in MSM in 2018 (41.2%) than in intravenous drug users (35.6%). In MSM, treatment at the acute phase represented 30.0% of treatments in 2018. Conclusions: A major shift in HCV epidemiology was observed in PLWH in France from 2012 to 2018, leading to a unique situation in which the major group of HCV transmission in 2018 was MSM. Clinical Trials Registration . NCT02898987. Abstract : A major shift in hepatitis C virus (HCV) epidemiology was observed in French persons living with human immunodeficiency virus (HIV) from 2012 to 2018, with men who have sex with men being the major group of HCV transmission. Three World Health Organization targets for HCV elimination have already been reached in HIV-HCV patients in France.